PEMAKNAAN SELF COMPASSION PADA TENAGA KESEHATAN DI JAKARTA UTARA MELALUI PENDEKATAN PSIKOLOGI ULAYAT - Clara Moningka (Universitas Bunda Mulia, 2013)
The purpose of this study was to determine how the meaning of self compassion in different cultures, especially health workers in North Jakarta when faced failure, suffering or disability themselves, and to analyse if self compassion expressed by Neff is applicable in Indonesia culture. This study uses indigenous psychology approach. This research employs thematic analysis techniques. This technique is applied to the data obtained through open ended questionnaire. The results of these adjustments can be sorted that the degree of the reaction is the overidentification (51.67%), mindfulness (39.17%), self kindness (1.67%), self judgment (6.67%), isolation (0.83%), and common humanity (0% ). Factors affecting self compassion like personality, gender, and cultural roles of parents also appeared on the respondent. In addition to these factors, the researchers also found some new factors affecting health workers in North Jakarta in the face of failure, suffering or feelings of inadequacy that the social environment, external pressure, occupation, education, age, high confidence, motivation and economy. The conclusion of this study is the theory proposed by Neff on self-compassion can be applied in the Indonesian cultural background, which research results obtained by researchers supported by the results of research Clara (2013) on The Meaning of Self Compassion and The Response Toward Failure in Our Society. This is because the themes that have obtained the same concept with the concept of the components as well as the factors that influence self-compassion Keywords: self compassion, health workers, indigenous psychology